2018
DOI: 10.1007/s00586-018-5689-7
|View full text |Cite
|
Sign up to set email alerts
|

Huge myxoid chondrosarcoma expanded into the thoracic cavity with spinal involvement

Abstract: A careful planning and a multidisciplinary collaboration make possible to perform en bloc resection even in apparently impossible cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Similarly, a systematic review reported that the negative margin rate obtained following en bloc resection of 229 primary spinal tumors was 86.1% ( 25 ), and a study from a single center of 220 spinal tumors that underwent en bloc resection found that the negative margin rate was 85.9% ( 23 ). Careful planning and efficient design of surgical procedures can be successful in obtaining oncologically appropriate margins, even in difficult cases ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a systematic review reported that the negative margin rate obtained following en bloc resection of 229 primary spinal tumors was 86.1% ( 25 ), and a study from a single center of 220 spinal tumors that underwent en bloc resection found that the negative margin rate was 85.9% ( 23 ). Careful planning and efficient design of surgical procedures can be successful in obtaining oncologically appropriate margins, even in difficult cases ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obstacles to en bloc resection of spinal tumors include regional anatomical limitations and large tumor volumes (6)(7)(8). Due to the lack of surrounding anatomical barriers over the surface of the vertebral body, bone tumors that break through the cortical bone and longitudinal ligament can easily grow into huge masses outside the spinal column (9). Factors associated with large tumor sizes include the long duration of symptoms before seeking medical care (sometimes from months to years) and recurrence after non-standard operations (e.g., curettage or intralesional resection).…”
Section: Introductionmentioning
confidence: 99%
“…A giant thoracic tumor is a kind of rare tumor clinically [1][2][3]. Because of its complicated pathological types and prognosis, there is no unified standard for the diagnosis and treatment, and surgical resection becomes the major clinical treatment means [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%